Deficient Treatment of Deficiency Claims: Gilmore Would Have Repented - Donald J. Rapson (Washington University Law Quarterly, 1997)
Part I of this Article examines the fair value rule in the context of Gilmore's perception of the commercial reasonableness concept. Part II discusses the reaction to, and progress of, the fair value proposal in the Article 9 Drafing Committee.
Keywords: Foreclosure; Judicial sales; Gilmore, Grant